Analisis Strategi Marketing Syariah Dan Kualitas Pelayanan Dalam Meningkatkan Volume Penjualan Kambing Aska Aqiqah - Shafira, Diah (Al-Sharf: Jurnal Ekonomi Islam, 2023)
This study aims to determine and analyze sharia marketing strategies and service quality in increasing sales volume of aska aqiqah goats. This study uses a qualitative research method that is descriptive in nature. The data collection method used is the method of observation, interviews and documentation, carried out on aska aqiqah goat breeders. With several informants, namely Mr. Suyadi, the owner of the aska aqiqah. The results of this study indicate that based on interviews with informants that sharia marketing strategies and service quality in increasing sales volume of aska aqiqah goats are very good at increasing sales at aska aqiqah farms. In the implementation of the aska aqiqah marketing strategy which is analyzed based on (four) variables in the sharia marketing mix (sharia marketing mix), namely products, prices, places and promotions have been implemented properly so as to increase the sales volume of aska aqiqah and on the application of service quality in increasing sales volume also very good.